Role of ART in Imprinting Disorders - Eroglu, Ali; Layman, Lawrence C. (Seminars in Reproductive Medicine, 2012)
Assisted reproductive technologies (ART) offer revolutionary infertility treatments for millions of childless couples around the world. Currently, ART accounts for 1 to 3% of annual births in industrialized countries and continues to expand rapidly. Except for an increased incidence of premature births, these technologies are considered safe. However, new evidence published during the past decade has suggested an increased incidence of imprinting disorders in children conceived by ART. Specifically, an increased risk was reported for Beckwith-Wiedemann syndrome (BWS), Angelman syndrome (AS), Silver-Russell syndrome, and retinoblastoma. In contrast, some studies have found no association between ART and BWS, AS, Prader-Willi syndrome, transient neonatal diabetes mellitus, and retinoblastoma. The variability in ART protocols and the rarity of imprinting disorders complicate determining the causative relationship between ART and an increased incidence of imprinting disorders. Nevertheless, compelling experimental data from animal studies also suggest a link between increased imprinting disorders and ART. Further comprehensive, appropriately powered studies are needed to better address the magnitude of the risk for ART-associated imprinting disorders. Large longitudinal studies are particularly critical to evaluate long-term effects of ART not only during the perinatal period but also into adulthood. An important consideration is to determine if the implicated association between ART and imprinting disorders is actually related to the procedures or to infertility itself.
Keywords: Epigenetics; genomic Imprinting; methylation; imprinting disorders; ART